PENDIDIKAN ISLAM DI SUDAN PASCA KONFLIK: STRATEGI REKONSTRUKSI DAN PENGUATAN NILAI KEISLAMAN - Mufti, Zaki Aulia; Rosyada, Dede; Zalnur, Muhammad; Gusmaweti, Gusmaweti; Effendi, Heri (LPPM STAI Muhammadiyah Probolinggo, 2025)
The prolonged conflict in Sudan has severely affected the Islamic education system, leading to infrastructure damage, declining quality of learning, and the erosion of Islamic values within society. This article aims to examine the reconstruction strategies of Islamic education in post-conflict Sudan and explore efforts to strengthen Islamic values through formal and non-formal educational pathways. The study employs a qualitative-descriptive method using a literature review approach, analyzing academic documents, international reports, and Sudanese national education policies. The findings reveal that reconstruction efforts include curriculum revitalization emphasizing peace and justice, re-training of religious teachers, and collaboration among the government, civil society, and religious institutions. Islamic education also functions as a strategic tool for promoting social reconciliation and strengthening societal cohesion. These findings affirm that Islamic education plays a central role not only in religious instruction but also in rebuilding a post-conflict society that is peaceful, inclusive, and grounded in moral values.